CLINICAL EFFICACY OF AYURVEDIC MANAGEMENT IN LUMBAR SPONDYLOSIS: A CASE STUDY - Vd. Sandeep Aggarwal (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Background: Lumbar spondylosis is a degenerative disorder affecting the lower spine, leading to chronic low back pain and restricted mobility. Conventional treatments often provide symptomatic relief but may have limitations in addressing the root cause. Ayurveda, with its holistic approach involving Shodhana (purificatory therapies) and Shamana (palliative measures), offers promising results in the management of degenerative spinal disorders.Objective: To assess the clinical efficacy of an Ayurvedic treatment protocol in the management of lumbar spondylosis through a single case study.Case Presentation:A 52-year-old male patient presented with complaints of chronic low back pain, stiffness, and radiating pain to the lower limbs, diagnosed as lumbar spondylosis based on clinical and radiological findings. The condition was correlated with Kati Graha and Vata Vyadhi in Ayurvedic classics. Intervention: The patient underwent a comprehensive Ayurvedic treatment protocol, including Abhyanga (medicated oil massage), Swedana (sudation therapy), Kati Basti (oil pooling on lumbar region), and Matra Basti (medicated enema), followed by Shamana Chikitsa with internal medications such as Dashamoola Kwatha, Rasna Saptaka Kwatha, and Yograj Guggulu for 30 days.Results: The patient showed significant improvement in pain reduction, increased lumbar flexibility, and enhanced quality of life. Visual Analogue Scale (VAS) scores decreased from 7 to 2, and Oswestry Disability Index (ODI) improved by 60% post-treatment.Conclusion: The case study highlights the potential of Ayurvedic therapies as an effective and safe management strategy for lumbar spondylosis. The integrative approach of Shodhana and Shamana therapies can be beneficial in managing degenerative spinal conditions.